DIFFERENTIATED APPROACH TO THE PRESERVATION OF THE ROOTS OF TEETH AND THEIR USE IN DENTAL PROSTHETICS - S.V. Irkha (Український стоматологічний альманах)
Actuality of theme. The problem of the maximum preservation of decayed teeth is the practical importance for the prevention of deformities dentition and alveolar process atrophy. In addition, the preservation of decayed teeth will prevent their removal from the consequences.